EXAMINING CURRICULUM NEEDS, TEACHING METHODS, AND TECHNOLOGY INTEGRATION FOR A COMPREHENSIVE APPROACH TO ENGLISH LANGUAGE EDUCATION - Pratiwi, Widya Rizky; Juhana, Juhana; Acfira, Lukytta Gusti; Sumbulatin, Sumbulatin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study explores the interplay between flexible curricula, innovative teaching methodologies, and technology integration in enhancing English language education, aiming to develop a comprehensive framework for effective language instruction. Employing a qualitative case study design, the research engaged a diverse group of educators and curriculum designers, facilitating in-depth discussions on their experiences and perceptions regarding curriculum flexibility and technology use in language teaching. The findings reveal a strong consensus among participants on the essential role of technology and adaptable curricula in promoting student engagement and communicative competence. Respondents highlighted technology's significance in fostering interactive learning environments, while emphasizing the necessity of flexible curricula to cater to diverse learner needs. This dual focus on technological and curricular adaptability indicates a vital shift toward more inclusive and responsive educational practices. The significance of this study lies in its contribution to the existing literature by providing insights into the collective impact of curriculum flexibility, pedagogical innovation, and technology integration on English language learning outcomes. Additionally, it offers practical recommendations for educators and policymakers to develop curricula that are not only technologically inclusive but also aligned with the dynamic demands of 21st-century learners. By addressing the complexities of language education in a digital context, this research underscores the importance of a cohesive approach to curriculum and instruction, paving the way for future investigations into effective language teaching practices across various educational settings.